Higher tax morale implies a higher optimal income tax rate - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2011)
We analyze the impact of (exogenous) tax morale on the optimal design of progressive income taxation. In our model, only universal basic income (transfer) is financed from a linear income tax and the financing of public goods is neglected. Each individual supplies labor and (un)declares earning, depending on his labor disutility and tax morale, respectively. Limiting the utilitarianism to the poorer parts of the population (defined by the welfare share), the optimal tax rate is an increasing function of the tax morale and a decreasing function of the welfare share.
Keywords: H21; H26; H41; D58; 330; tax morale; progressive income tax; undeclared earning; labor supply; income redistribution; Steuermoral; Wirkungsanalyse; Steuerprogression; Einkommensteuer; Arbeitsangebot; Soziale Wohlfahrtsfunktion